Non-observation RINEX compression - BEZRUČKA, Juraj (Contributions to Geophysics and Geodesy, 2013)
RINEX format is a result of an effort to standardize exchanging GNSS related data in human readable receiver independent format. Besides observation data, RINEX is also de facto standard for exchanging navigation message or meteorological data. The paper describes simple compression methods for navigation messages and meteorological data files. Both formats have their specific features, therefore different methods were used. Followed by standard compression the algorithms reduce the file size by more than 20 percent compared to standard compression. Thanks to the properties of weather and regular parameter observations it allows to reduce the file size of meteorological RINEX to a mere fraction of its original size.